Analisis Pembangunan Daerah Istimewa Yogyakarta: Keterkaitan Keistimewaan, Kinerja Sosial Ekonomi Dan Tantangan Struktural - Nasywaa Hadaina Sabila Husnan; Putri Imeida Nazwa; Fadjar Tri Sakti (STISIP Margarana, 2026)
The core problem addressed in this study is a development paradox in the Special Region of Yogyakarta: strong achievements in human development and macroeconomic performance coexist with persistently high poverty and income inequality, alongside intensifying structural pressures related to spatial planning, land governance, and environmental management. This study aims to assess the effectiveness of the Special Privileges Fund of the Special Region of Yogyakarta in promoting equitable development, examine how macroeconomic performance relates to inequality, and identify the need to integrate spatial planning and land governance to support sustainable development. A descriptive qualitative approach is employed through the synthesis of secondary official statistics and a review of policy regulations, interpreted using cultural-based development, sustainable development, and strategic territorial development perspectives. The findings indicate that program implementation demonstrates strong budget execution, yet the benefits have not translated into inclusive multiplier effects, resulting in uneven distribution of development gains. Weak spatial control and land-market dynamics increase the risk of spatial injustice and social vulnerability, while environmental management gaps threaten long-term sustainability. The study concludes that policy reorientation is required to better align special-privileges programs with equity goals, strengthen spatial and land governance that protects low-income groups, and embed environmental resilience as a foundation for sustainable regional development.